1999
DOI: 10.1007/s004649900997
|View full text |Cite
|
Sign up to set email alerts
|

Safety of preoperation endoscopic tattoo with india ink for identification of colonic lesions

Abstract: Preoperative mucosal tattooing with india ink is recommended as a safe and necessary procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 18 publications
5
54
1
2
Order By: Relevance
“…These methods include barium enema, computed tomography colonography, placement of mucosal clips, and intra-operative colonoscopy [4]. The barium enema historically has been the modality used to localize lesions for surgery but is increasingly unreliable [5]. While it is a good method for localizing exophytic and stenosing lesions, it is less effective for localizing early or flat tumors [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These methods include barium enema, computed tomography colonography, placement of mucosal clips, and intra-operative colonoscopy [4]. The barium enema historically has been the modality used to localize lesions for surgery but is increasingly unreliable [5]. While it is a good method for localizing exophytic and stenosing lesions, it is less effective for localizing early or flat tumors [6].…”
Section: Discussionmentioning
confidence: 99%
“…While it is a good method for localizing exophytic and stenosing lesions, it is less effective for localizing early or flat tumors [6]. Preoperative location of a lesion by measuring centimeters of instrument introduced into the rectum is a poor method due to variability in length of colon and looping of the scope within the colon [5]. Localization with computed tomography colonography is useful for detecting not only the primary tumor but also synchronous colon lesions, provides additional information about regional and distant metastatic disease, the depth of wall invasion, and the precise location of the lesion in the colon prior to surgery [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although three studies with a total of 264 patients who underwent colonoscopic tattooing reported no fever, abdominal pain, or any major complications [64][65][66], a systematic review of 447 patients with colonoscopic tattooing described 5 cases of complications with only one was an overt clinical complication (22.3 per 10,000 tattooing) [67].…”
Section: Colonoscopic Tattooingmentioning
confidence: 99%